Classifying Ditch and Stream Channels Mapped From High-Resolution Digital Elevation Models Using Machine Learning - Busarello, Mariana; Lidberg, William; Ågren, Anneli; Westphal, Florian (Swedish University of Agricultural Sciences, 2026)
This data contains the digital elevation models with 0.5 m resolution and polyline shapefiles with the location of channels from the 12 study areas used in this study.

It also has the scripts to generate the datasets used to train the machine learning model to classify channels into ditches and streams, and calculate the hydrological indices. The code to train the model is also included, along with the models obtained.

For the ground truth data, the channels were mapped differently based on their type: ditches were manually digitized based on the visual analysis of some topographic indices and orthophotos obtained from the DEM. Streams were mapped by initially detecting all natural channel heads, then tracing the downstream channels, and finally manually editing them based on orthophotos.

We recommend using Docker to set the environment.

Den här datamängden innehåller digitala höjdmodeller i 0,5 meters upplösningoch polyline-shapefiler med placeringen av kanaler från de 12 studieområdena som används i denna studie.

Den innehåller också koden för att generera datamängderna som används för att träna maskinlärningsmodellerna som används för att klassificera diken och vattendrag, och beräkna hydrologiska index. Koden för att träna modellen ingår också, tillsammans med de erhållna modellerna.

För markdata kartlades kanalerna på olika sätt baserat på deras typ: diken digitaliserades manuellt baserat på visuell analys av vissa topografiska index och ortofoton som erhållits från DEM.
Vattendrag kartlades genom att initialt detektera alla naturliga kanalhuvuden, sedan spåra de nedströms kanalerna och slutligen manuellt redigera dem baserat på ortofoton.

Vi rekommenderar att man använder Docker för att ställa in miljön.
Klassificering av diken och vattendragskanaler kartlagda från högupplösta digitala höjdmodeller med hjälp av maskininlärning
Keywords: RIVERS/STREAMS; WATER CHANNELS; digital elevation model; Hydrography; Hydrografi; ditches; diken; machine learning; maskininlärning; artificial intelligence; artificiell intelligens; lidar; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Physical Geography; Naturgeografi; Soil Science; Markvetenskap; Imagery / Base Maps / Earth Cover; Arealtäckande bilder och bakgrundskartor; Geoscientific Information; Geovetenskap; Elevation; Höjddata; Location; Positionering; Inland Waters; Sjöar och vattendrag